تط يق نظرية المصلحة في إدارة الأراضي الوقفية - Zahro, Khurun’in; Jamal, Mulyono; Al Faruqi, Musta’an (Karabük Üniversitesi, 2022)
The most endowed property in Indonesia is the land, but it was not managed by an invested administration, so that an important role in the possibility of the economy did not appear from it. As for the endowment lands, it is one of the investment endowments and it has the interest of the nation if it is managed with a fully professional management. This research is a qualitative desk research to find out about the application of the Maslahah theory in the management of endowment lands. The results of this research are that the application of the theory of interest in the management of endowment lands is inseparable from the five colleges of religion. Waqf is money, so it should be preserved and developed by the most successful means. The proof of this is the existence of endowment land management of many types, such as in the religious field such as prayer places and mosques, in the educational field such as schools and institutes, in the health field such as hospitals, in the economic field such as apartments, treasury and finance, shops, and in the social field such as cemeteries, offices and so on.
Keywords: الأراضي الوقفية; الإدارة; الناظر; المصلحة; Endowment Lands; Management; Nadzir; Maslahah